Analisis User Experience Tiktok Shop Menggunakan Framework Heart dan Importance Performance Analysis - theresiawati, theresiawati; Ananda Alvi Al Fadhli Josephine; Henki Bayu Seta; Rudhy Ho Purabaya (SOTVI - Society of Visual Informatics, 2024)
The rapid evolution of social media usage in Indonesia, particularly on TikTok, has marked a significant shift in online interaction. Despite initial controversies over negative content, TikTok's popularity surged in 2019 due to features such as the For You Page (FYP), dance challenges, and the increased online activity during the COVID-19 pandemic. Expanding its scope, TikTok introduced e-commerce features, including TikTok Shop, positioning itself as one of Indonesia's leading social commerce platforms. This study analyzes the user experience (UX) of TikTok Shop using the HEART framework (Happiness, Engagement, Adoption, Retention, and Task Success) combined with Importance Performance Analysis (IPA). Data was collected through questionnaires distributed to TikTok Shop users to identify key indicators for enhancing user experience and correlating these with the user interface (UI) of the TikTok Shop menu. Results revealed significant findings in the Cartesian diagram, with key metrics in Quadrant II including H1 (3.767%), H3 (2.31%), A1 (3.767%), and T7 (1.856%). Redesign recommendations were implemented for items categorized as Action and positioned in Quadrants II and III. Post-redesign testing showed a notable improvement, with an average performance increase of 12.1% compared to the initial evaluation. These findings offer insights into optimizing the TikTok Shop interface to enhance user satisfaction and engagement.